(untitled) (Sociologisk Forskning, 2024)
This article brings Bourdieu’s concept of cultural capital into dialogue with critical race and whiteness studies and migration studies. It focuses on the ways in which whiteness as an analytical category is associated with a recognised set of privileges in terms of nationality, citizenship, knowledge, and mobility; assets that open up new ways of producing and reproducing cultural capital. As a kind of objectified and institutionalised capital, whiteness is materialised through institutions, passports and visa policies, all of which imply that individuals and groups classified as white can feel “at home” almost anywhere in the world. However, between a globalised history of racialisation linked to European colonisation and contemporary neoliberal competition, perceptions of whiteness are changing in transnational social space. In other words, whiteness as cultural capital is on the one hand intertwined with histories of colonial racial structures, and on the other hand it is challenged by global neoliberalism, where Asian notions of whiteness in particular cast European whiteness in a new light.